Modern recording techniques - Huber, David Miles; Runstein, Robert E. (New York London Routledge, Taylor & Francis Group, 2018)
"Modern Recording Techniques is the bestselling, authoritative guide to sound and music recording. Whether you’re just starting out or are looking for a step-up in the industry, Modern Recording Techniques provides an in-depth read on the art and technologies of music production. It’s a must-have reference for all audio bookshelves. Using its familiar and accessible writing style, this ninth edition has been fully updated, presenting the latest production technologies and includes an in-depth coverage of the DAW, networked audio, MIDI, signal processing and much more. A robust companion website features video tutorials, web-links, an online glossary, flashcards, and a link to the author’s blog. Instructor resources include a test bank and an instructor’s manual. The ninth edition includes:Updated tips, tricks and insights for getting the best out of your studio; An introduction to the Apple iOS in music production; Introductions to new technologies and important retro studio techniques; The latest advancements in DAW systems, signal processing, mixing and mastering."--Provided by publisher.
Chapter 1: Introduction -- Chapter 2: Sound and Hearing -- Chapter 3: Studio Acoustics and Design -- Chapter 4: Microphones: Design and Application -- Chapter 5: The Analog Tape Recorder -- Chapter 6: Digital Audio Technology -- Chapter 7: The Digital Audio Workstation -- Chapter 8: Groove Tools and Techniques -- Chapter 9: MIDI and Electronic Music Technology -- Chapter 10: The iOS in Music Production -- Chapter 11: Multimedia and the Web -- Chapter 12: Synchronization -- Chapter 13: Amplifiers -- Chapter 14: Power- and Ground-Related Issues -- Chapter 15: Signal Processing -- Chapter 16: Noise Reduction -- Chapter 17: The Art and Technology of Mixing -- Chapter 18: Monitoring -- Chapter 19: Immersive Audio (5.1 and Beyond) -- Chapter 20: Mastering -- Chapter 21: Product Manufacture and Distribution -- Chapter 22: Studio Tips and Tricks -- Chapter 23: Yesterday, Today and Tomorrow
Keywords: Sound -- Recording and reproducing; Magnetic recorders and recording; Digital audiotape recorders and recording